Helping students gain understanding and self-confidence in algebra.
R515 wrote:the equation is
x^2 - y^2 =12 where y = x-2 .
R515 wrote:none of the methodology (e.g. factorisation or quadratic formula) in her notes or the text books give me the right answer.
R515 wrote:Through factorisation, x = -2 which is wrong
R515 wrote:x^2 - (x-2)^2 = 12
x^2 - (x-2)(x-2) = 12
x^2 -x^2 -4x +4 = 12
R515 wrote:is it the effect of removing the bracket on
x^2 -(x^2 +4x -4) =12
that turns +4x into -4x and -4 into +4 then as this is what makes it work out right with x=4 ?